Analyzing the gut liver axis: a dual role of the microbiome in the genesis, progression, and treatment of liver cell carcinoma - Li, Qianzhu; Liu, Yafang (Frontiers in Microbiology, 2025)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality worldwide, and the poor prognosis highlights the pressing need for innovative therapeutic strategies. The gut-liver axis, a critical bidirectional pathway linking the gut microbiota to the liver, plays a pivotal role in HCC pathogenesis. This review systematically delineates current evidence on how gut dysbiosis, compromised intestinal barrier function, and resultant microbial metabolites (e.g., bacterially metabolized bile acids) drive hepatocarcinogenesis via specific signaling pathways, while also addressing the loss of protective effects due to the depletion of beneficial microbes. Moving beyond descriptive summaries, this article focuses on elucidating the core molecular mechanisms of microbiome-regulated HCC—a key knowledge gap that remains unaddressed—and reconciles conflicting findings into a unified framework. We further explore the translational potential of microbiome signatures as non-invasive biomarkers and evaluate microbiota-targeting interventions (e.g., probiotics, dietary modulation, fecal microbiota transplantation) for enhancing treatment efficacy. Ultimately, this review aims to provide a clear roadmap for developing microbiome-based precision medicine in HCC, with the goal of improving clinical management and patient outcomes.